Pengembangan E-Modul Berbasis Canva Pada Tema Sehat Itu Penting Subtema Peredaran Darahku Sehat - Mutiara Zahra; Elly Sukmanasa; Lina Novita (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
Based on the results of observations, the problems found were that students had not received innovative teaching materials, students were still using theme books, bupenas in the learning process and also teachers had not developed electronic and application-based teaching materials. (2) knowing the feasibility of a Canva-based e-module with validation tests by media, material, language experts, and student responses. The results of this development research are in the form of a percentage of the validation test scoring by the material expert validator with a score of 87%, media experts at 95%, category and linguists giving a score of 100% with the very feasible category. It can be concluded that the development of Canva-based e-modules on theme 1, sub-theme 1, learning 1 is appropriate for use by teachers and students in the learning process.